Skip to content

Advertisement

  • Research
  • Open Access

Geraghty-type theorems in modular metric spaces with an application to partial differential equation

Advances in Difference Equations20122012:83

https://doi.org/10.1186/1687-1847-2012-83

  • Received: 3 May 2012
  • Accepted: 20 June 2012
  • Published:

Abstract

In this article, we prove some fixed point theorems of Geraghty-type concerning the existence and uniqueness of fixed points under the setting of modular metric spaces. Also, we give an application of our main results to establish the existence and uniqueness of a solution to a nonhomogeneous linear parabolic partial differential equation in the last section.

Mathematics Subject Classification (2010): 47H10, 54H25, 35K15.

Keywords

  • modular metric space
  • ordered set
  • Geraghty's theorem
  • initial value problems
  • parabolic equation.

Introduction and preliminaries

Throughout this article, let + denote the set of all positive real numbers and let + denote the set of all nonnegative real numbers.

Since the year 1922, Banach's contraction principle, due to its simplicity and applicability, has became a very popular tool in modern analysis, especially in nonlinear analysis including its applications to differential and integral equations, variational inequality theory, complementarity problems, equilibrium problems, minimization problems and many others. Also, many authors have improved, extended and generalized this contraction principle in several ways (see e.g. [110]).

In 1973, Geraghty [11] gave an interesting generalization of the contraction principle using the class S of the functions β: + [0, 1) satisfying the following condition:
β ( t n ) 1 implies  t n 0 .
Theorem 1.1. [11]Let (X, d) be a complete metric space and f be a self-mapping on X such that there exists β S satisfying
d ( f x , f y ) β ( d ( x , y ) ) d ( x , y )
(1.1)

for all x, y X. Then the sequence {x n } defined by x n = fxn- 1for each n ≥ 1 converges to the unique fixed point of f in X.

Later, Amini-Harandini et al. [12] extended Geraghty's fixed point theorem to the setting of partially ordered metric spaces as follows:

Theorem 1.2. [12]Let (X, ) be a partially ordered metric set and suppose that there exists a metric d in X such that (X, d) is a complete metric space. Let f be a nondecreasing self-mapping on X which satisfies the inequality (1.1) whenever x, y X are comparable. Assume that f is either continuous or
i f a n o n d e c r e a s i n g s e q u e n c e x n c o n v e r g e s t o x * , t h e n x n x * f o r e a c h n 1 .
(1.2)
If, additionally, the following condition is satisfied:
f o r a n y x , y X , t h e r e e x i s t s z X w h i c h i s c o m p a r a b l e t o b o t h x a n d y ,
(1.3)

then the sequence {x n } converges to the unique fixed point of f in X.

Let Ψ denote the class of functions ψ: + + satisfying the following conditions:
  1. (a)

    ψ is nondecreasing.

     
  2. (b)

    ψ is continuous.

     
  3. (c)

    ψ(t) = 0 if and only if t = 0.

     

Using this class, Eshaghi Gordji et al. [13] extended the Theorem 1.2 as follows:

Theorem 1.3. [13]Let (X, ) be a partially ordered metric set and suppose that there exists a metric d in X such that (X, d) is a complete metric space. Let f be a nondecreasing self-mapping on X such that there exists x0 X with x0 fx0. Suppose that there exist β S and ψ Ψ such that
ψ ( d ( f x , f y ) ) β ( ψ ( d ( x , y ) ) ) ψ ( d ( x , y ) ) ,

whenever x, y X are comparable. Assume also that the condition (1.2) holds. Then f has a fixed point.

On the other hand, in 2010, Chistyakov [14] introduced the notion of a modular metric space which is raised in an attempt to avoid some restrictions of the concept of a modular space (for the literature of a modular space, see e.g. [1521] and references therein). Some of the early investigations on metric fixed point theory in this space refer to [2224].

For the rest of this section, we present some notions and basic facts of modular metric spaces.

Definition 1.4. [14] Let X be a nonempty set. A function ω: + × X × X → + {} is said to be a metric modular on X if, for all x, y, z X, the following conditions hold:
  1. (a)

    ω λ (x, y) = 0 for all λ > 0 if and only if x = y.

     
  2. (b)

    ω λ (x, y) = ω λ (y, x) for all λ > 0.

     
  3. (c)

    ω λ+μ(x, y) ≤ ω λ (x, z) + ω μ (z, y) for all λ, μ > 0.

     

For any x ι X, the set X ω (x ι ) = {x X: lim λ→∞ ω λ (x, x ι ) = 0} is called a modular metric space generated by x ι and induced by ω. If its generator x ι does not play any role in the situation (that is, X ω is independent of generators), we write X ω instead of X ω (x ι ).

Observe that a metric modular ω on X is nonincreasing with respect to λ > 0. We can simply show this assertion using the condition (c). For any x, y X and 0 < μ < λ, we have
ω λ ( x , y ) ω λ - μ ( x , x ) + ω μ ( x , y ) = ω μ ( x , y ) .
(1.4)
For any x, y X and λ > 0, we set
ω λ + ( x , y ) : = lim ϵ 0 ω λ + ϵ ( x , y ) , ω λ - ( x , y ) : = lim ϵ 0 ω λ - ϵ ( x , y ) .
Consequently, from (1.4), it follows that
ω λ + ( x , y ) ω λ ( x , y ) ω λ - ( x , y ) .

For any x, y X, if a metric modular ω on X possesses a finite value and ω λ (x, y) = ω μ (x, y) for all λ, μ > 0, then d(x, y): = ω λ (x, y) is a metric on X.

Later, Chaipunya et al. [23] has altered the notion of convergent and Cauchy sequences in modular metric spaces under the direction of Mongkolkeha et al. [24].

Definition 1.5. [23, 24] Let X ω be a modular metric space and {x n } be a sequence in X ω .
  1. (1)

    A point x X ω is called a limit of {x n } if, for each λ, ϵ > 0, there exists n 0 such that ω λ (x n , x) < ϵ for all n ≥ n 0. A sequence that has a limit is said to be convergent (or converges to x), which is written as lim n→∞ x n = x.

     
  2. (2)

    A sequence {x n } in X ω is said to be a Cauchy sequence if, for each λ, ϵ > 0, there exists n 0 such that ω λ (x n , x m ) < ϵ for all m, n ≥ n 0.

     
  3. (3)

    If every Cauchy sequences in X converges, X is said to be complete.

     

In this article, we prove a generalization of Geraghty's theorem which also improves the result of Eshagi Gordji et al. [13] under the influence of a modular metric space. An application to partial differential equation is also provided.

Main results

Before stating our main results, we first introduce the following classes for a more convenience of usage.

For each n , let S n denote the class of n-tuples of functions (β1, β2, ..., β n ), where for each i {1, 2, ..., n}, β i : + {} [0, 1) and the following implication holds:
β ( t k ) : = β 1 ( t k ) + β 2 ( t k ) + + β n ( t k ) 1 implies  t k 0 .
Actually, Geraghty's class  S is equivalent to the class S 1 when ∞ is not considered. It follows that, for each m {1, 2, ..., n}, if ( β 1 , β 2 , , β m ) S m , then ( β 1 , β 2 , , β m , θ , θ , , θ n - m entries ) S n , where θ denotes the zero function. Also, note that, if ( β , β , , β ) n entries S n , then we also have the following:
β ( t k ) 1 n implies  t k 0 .

Besides, if ( β 1 , β 2 , β n ) S n , then π ( ( β 1 , β 2 , β n ) ) S n , where π((β1, β2 ..., β n )) is a permutation of (β1, β2 ..., β n ). It is also important to know that, if ( β 1 , β 2 , β n ) S n , then ( β n 1 , β n 2 , , β n m ) S m for each m {1, 2, ..., n}, where each β n i is selected from {β1, β2, ..., β n } and β n i β n j for all i, j {1, 2, ..., m}.

Let Ψ ̄ denote the class of functions ψ: + {} + {} satisfying the following conditions:
  1. (a)

    If 0 < t < ∞, then ψ(t) < ∞.

     
  2. (b)

    ψ | + Ψ .

     

Now, we are ready to give our main results in this article.

Theorem 2.1. Let X ω be a complete modular metric space with a partial ordering and f be a self-mapping on X ω such that, for each λ > 0, there exists η(λ) (0, λ) such that
ψ ( ω λ ( f x , f y ) ) α ( ψ ( ω λ ( x , y ) ) ) ψ ( ω λ + η ( λ ) ( x , y ) ) + β ( ψ ( ω λ ( x , y ) ) ) ψ ( ω λ ( x , f x ) ) + γ ( ψ ( ω λ ( x , y ) ) ) ψ ( ω λ ( y , f y ) ) ,
(2.1)
where ψ Ψ ̄ and ( α , β , γ ) S 3 with α(t) + 2 max{supt≥ 0β(t), supt≥ 0γ(t)} < 1. Assume also that the condition (1.2) holds. If there exists x0 X ω such that ω λ (x0, fx0) < ∞ for all λ > 0, then the following hold:
  1. (1)

    f has a fixed point x X ω .

     
  2. (2)

    The sequence {f n x 0} converges to x .

     
Proof. It is clear that the sequence {f n x0} is nondecreasing. Assume that, for each n ≥ 1, there exists λ n > 0 such that ω λ n ( f n x 0 , f n + 1 x 0 ) 0 . Otherwise, the proof is complete. For each n ≥ 1, if 0 < λ ≤ λ n , then we also have ω λ (f n x0, fn+1x0) ≠ 0. Since f n x0fn+1x0, for any 0 < λ ≤ λ n , we have
ψ ( ω λ n ( f n x 0 , f n + 1 x 0 ) ) ψ ( ω λ ( f n x 0 , f n + 1 x 0 ) ) α ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ + η ( λ ) ( f n - 1 x 0 , f n x 0 ) ) + β ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) + γ ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ ( f n x 0 , f n + 1 x 0 ) ) α ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) + β ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) + γ ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ ( f n x 0 , f n + 1 x 0 ) ) ,
which implies that
ψ ( ω λ ( f n x 0 , f n + 1 x 0 ) ) α ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) + β ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) 1 - γ ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ψ ω λ ( x 0 , f x 0 )) < .
Therefore, {ψ(ω λ (f n x0, fn+1x0))} is nonincreasing and bounded below. So, the sequence converges to some number r ≥ 0. Assume r > 0. Observe that
ψ ( ω λ ( f n x 0 , f n + 1 x 0 ) ) α ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) + β ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) )  + γ ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) .
Taking n → ∞, we have
1 lim  inf n α ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) + β ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) )  + γ ( ψ ( ω λ ( f n - 1 x 0 , f n x 0 ) ) ) .
So, we have lim n→∞ ψ(ω λ (fn-1x0, f n x0)) = 0 and hence
lim n ω λ ( f n - 1 x 0 , f n x 0 ) = 0 ,

which is a contradiction of our assumption. Therefore, lim n→∞ ψ(ω λ (f n x0, fn+1x0)) = 0 and so, we have lim n→∞ ω λ (f n x0, fn+1x0) = 0. Moreover, we have lim n→∞ ω λ (f n x0, fn+1x0) = 0 for all λ > 0.

Next, we show that {f n x0} is a Cauchy sequence. Assume the contrary. So, there exists λ0, ϵ0> 0 for which we can define two subsequences { f m k x 0 } and { f n k x 0 } of the sequence {f n x0} such that, for any n k > m k > k, ω λ 0 ( f m k x 0 , f n k x 0 ) ϵ 0 , but ω λ 0 ( f m k x 0 , f n k - 1 x 0 ) < ϵ 0 . Now, since f m k x 0 f n k x 0 , we observe that
ψ ( ϵ 0 ) ψ ( ω λ 0 ( f m k x 0 , f n k x 0 ) ) α ( ψ ( ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) ) ) ψ ( ω λ 0 + η ( λ 0 ) ( f m k - 1 x 0 , f n k - 1 x 0 ) ) + β ( ψ ( ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) ) ) ψ ( ω λ 0 ( f m k - 1 x 0 , f m k x 0 ) ) + γ ( ψ ( ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) ) ) ψ ( ω λ 0 ( f n k - 1 x 0 , f n k x 0 ) ) ψ ( ω η ( λ 0 ) ( f m k - 1 x 0 , f m k x 0 ) + ω λ 0 ( f m k x 0 , f n k - 1 x 0 ) ) + ψ ( ω λ 0 ( f m k - 1 x 0 , f m k x 0 ) ) + ψ ( ω λ 0 ( f n k - 1 x 0 , f n k x 0 ) ) ψ ( ω η ( λ 0 ) ( f m k - 1 x 0 , f m k x 0 ) + ϵ 0 ) + ψ ( ω λ 0 ( f m k - 1 x 0 , f m k x 0 ) ) + ψ ( ω λ 0 ( f n k - 1 x 0 , f n k x 0 ) ) .
Letting k → ∞, we obtain that lim k ψ ( ω λ 0 ( f m k x 0 , f n k x 0 ) ) = ψ ( ϵ 0 ) . So, we have
lim k ω λ 0 ( f m k x 0 , f n k x 0 ) = ϵ 0 .
Observe again that
ψ ( ω λ 0 ( f m k x 0 , f n k x 0 ) ) ψ ( ω λ 0 + η ( λ 0 ) ( f m k - 1 x 0 , f n k - 1 x 0 ) ) + ψ ( ω λ 0 ( f m k - 1 x 0 , f m k x 0 ) ) + ψ ( ω λ 0 ( f n k - 1 x 0 , f n k x 0 ) ) ψ ω η ( λ 0 ) 2 ( f m k - 1 x 0 , f m k x 0 ) + ω λ 0 ( f m k x 0 , f n k x 0 ) + ω η ( λ 0 ) 2 ( f n k x 0 , f n k - 1 x 0 )  + ψ ( ω λ 0 ( f m k - 1 x 0 , f m k x 0 ) )  + ψ ( ω λ 0 ( f n k - 1 x 0 , f n k x 0 ) ) .
Letting k → ∞, we deduce that lim k ψ ( ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) ) = ψ ( ϵ 0 ) . Similarly, we have
lim k ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) = ϵ 0 .
Thus, it follows that
1 lim  inf k  α ( ψ ( ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) ) ) .
Therefore, we conclude that lim k ψ ( ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) ) = 0 , which implies that
lim k ω λ 0 ( f m k - 1 x 0 , f n k - 1 x 0 ) = 0 .

This is a contradiction. Therefore, it follows that {f n x0} is a Cauchy sequence. Due to the completeness of X ω , {f n x0} converges to some point x X ω .

Now, we show that x is a fixed point of f. Let λ > 0 be arbitrary. By virtue of the condition (1.2), we consider that
ψ ω λ ( f n + 1 x 0 , f x ) ψ ( ω λ ( f n x 0 , x ) ) + ψ ( ω λ ( f n x 0 , f n + 1 x 0 ) ) .

Letting n → ∞, we obtain that ψ(ω λ (x , fx ) 0 for all λ > 0. Therefore, x is a fixed point of f. ■

Theorem 2.2. Additional to the Theorem 2.1, if ψ is subadditive and the following condition holds:
f o r a n y x , y X ω , t h e r e e x i s t s w X ω w i t h w f w a n d ω λ w , f w < f o r a l l λ > 0 s u c h t h a t w i s c o m p a r a b l e t o b o t h x a n d y ,
(2.2)

then the fixed point in Theorem 2.1 is unique.

Proof. By Theorem 2.1, we know that f has a fixed point x X ω . Assume that y X ω is also another fixed point of f. Thus, we can find w X ω with w fw and comparable to both x and y . It follows that f n w is comparable with both x and y for each n . Observe that, for any λ > 0,
ψ ( ω λ ( f n + 1 w , x )) = ψ ( ω λ ( f n + 1 w , f x )) α ( ψ ( ω λ ( f n w , x ) ) ) ψ ( ω λ ( f n w , x ) ) + β ( ψ ( ω λ ( f n w , x ) ) ) ψ ( ω λ ( f n w , f n + 1 w ) ) α ( ψ ( ω λ ( f n w , x ) ) ) ψ ( ω λ ( f n w , x ) ) + β ( ψ ( ω λ ( f n w , x ) ) ) ψ ( ω λ ( f n w , x ) ) + β ( ψ ( ω λ ( f n w , x ) ) ) ψ ( ω λ ( x , f n + 1 w ) ) .
(2.3)
Therefore, without loss of generality, we have
ψ ( ω λ ( f n + 1 w , x )) α ( ψ ( ω λ ( f n w , x ) ) ) + β ( ψ ( ω λ ( f n w , x ) ) ) 1 - β ( ψ ( ω λ ( f n w , x ) ) ) ψ ( ω λ ( f n w , x ) ) ψ ( ω λ ( f n w , x ) ) ψ ( ω λ ( w , x ) ) < .
Therefore, {ψ(ω λ (f n w, x ))} is nonincreasing and bounded below. So, it converges to some real number h ≥ 0. Assume that h > 0. According to the proof of Theorem 2.1, we know that lim n→∞ ω λ (f n w, fn+1w) = 0 for all λ > 0. Thus, letting n → ∞ in the inequality (2.3), we have
1 lim  inf n  α ( ψ ( ω λ ( f n w , x ) ) ) .

Thus, we have {f n w} converges to x . Similarly, we obtain that {f n w } converges also to y . Since the limit is unique, we have x = y . This contradicts our assumption. Therefore, the theorem is proved. ■

Corollary 2.3. Additional to Theorem 2.1, if X ω is totally ordered, then the fixed point in Theorem 2.1 is unique.

Proof. Since X ω is totally ordered, the condition (2.2) is satisfied. Thus, applying Theorem 2.2, we obtain the result. ■

The following two corollaries nicely broaden the results in [24] (see Theorems 3.2 and 3.6 [24]).

Corollary 2.4. Let X ω be a complete modular metric space with a partial ordering and f be a self-mapping on X ω such that, for any λ > 0, there exists η(λ) (0, λ) such that
ψ ( ω λ ( f x , f y ) ) α ( ψ ( ω λ ( x , y ) ) ) ψ ( ω λ + η ( λ ) ( x , y ) ) ,

where α S and ψ Ψ ̄ . Assume also that f is continuous or the condition (1.2) holds. Then f has a fixed point in X ω . Moreover, if the condition (2.2) is satisfied, the fixed point is unique.

Proof. Since α S , we have ( α , θ , θ ) S 3 . Thus, apply Theorems 2.1 and 2.2, we have the conclusion. ■

Corollary 2.5. Let X ω be a complete modular metric space with a partial ordering and f be a self-mapping on X ω such that, for any λ > 0, there exist ζ(λ), μ(λ) (0, λ) such that
ψ ( ω λ ( f x , f y ) ) β ( ψ ( ω λ ( x , y ) ) ) ψ ( ω λ ( x , f x ) ) + γ ( ψ ( ω λ ( x , y ) ) ) ψ ( ω λ ( y , f y ) ) ,

where ψ Ψ ̄ and ( β , γ ) S 2 with max{supt≥ 0β(t), supt≥ 0γ(t)} < 1. Assume also that f is continuous or that the condition (1.2) holds. Then f has a fixed point in X ω . Moreover, if the condition (2.2) is satisfied, the fixed point is unique.

Proof. Since ( β , γ ) S 2 , we have ( θ , β , γ ) S 3 . Thus, apply Theorems 2.1 and 2.2, we have the conclusion. ■

Applications

In this section, we give an application of our theorems to establish the existence and uniqueness of a solution to a nonhomogeneous linear parabolic partial differential equation satisfying a given initial condition.

Consider the following initial value problem
u t ( x , t ) = u x x ( x , t ) + F ( x , t , u ( x , t ) , u x ( x , t ) ) , - < x < , 0 < t T u ( x , 0 ) = φ ( x ) 0 , - < x < ,
(3.1)

where we assume φ to be continuously differentiable such that φ and φ' are bounded and F is continuous.

By a solution of the system (3.1), we meant a function u ≡ u(x, t) defined on × I, where I: = [0, T], satisfying the following conditions:
  1. (a)

    u, u t , u x , u xx C( × I).

     
  2. (b)

    u and u x are bounded in × I.

     
  3. (c)

    u t (x, t) = u xx (x, t) + F(x, t, u(x, t), u x (x, t)) for all (x, t) × I.

     
  4. (d)

    u(x, 0) = φ(x) for all x .

     
Now, we consider the following space:
Ω : = { u ( x , t ) : u , u x C ( × I ) and || u | | < } ,
where
u : = sup x , t I ǀ u ( x , t ) ǀ + sup x , t I ǀ u x ( x , t ) ǀ .
Obviously, the function ω: + × Ω × Ω → + given by
ω λ ( x , y ) : = 1 1 + λ | | u - v | |
is a metric modular on Ω. Clearly, the set Ω ω is a complete modular metric space independent of generators. Define a partial ordering on Ω ω by
u , v Ω ω , u v u ( x , t ) v ( x , t ) and u x ( x , t ) v x ( x , t ) at each  ( x , t ) × I .

Taking a nondecreasing sequence {u n } in Ω ω converging to u Ω ω . For any (x, t) × I,

we have
u 1 ( x , t ) u 2 ( x , t ) u n ( x , t )
and
( u 1 ) x ( x , t ) ( u 2 ) x ( x , t ) ( u n ) x ( x , t ) .
Since the sequences {u n (x, t)} and {(u n ) x (x, t)} converges to u(x, t) and u x (x, t), respectively, it follows that, for any (x, t) × I,
u n ( x , t ) u ( x , t ) and ( u n ) x ( x , t ) u x ( x , t )

for all n ≥ 1. Therefore, u n u for all n ≥ 1. So, the space Ω ω satisfies the condition (1.2).

Theorem 3.1. Consider the problem (3.1) and assume the following:
  1. (1)

    For any c > 0 with |s| < c and |p| < c, the function F (x, t, s, p) is uniformly Hölder continuous in X and t for each compact subset of × I.

     
  2. (2)
    There exists a constant c F ( T + 2 π - 1 2 T 1 2 ) - 1 such that, for any λ > 0, there exists η(λ) (0, λ) such that
    0 1 1 + λ [ F ( x , t , s 2 , p 2 ) - F ( x , t , s 1 , p 1 ) ] c F 1 1 + λ + η ( λ ) ρ Ξ s 2 - s 1 + p 2 - p 1 1 + λ + 1 1 + λ σ Ξ s 2 - s 1 + p 2 - p 1 1 + λ
     
for all (s1, p1), (s2, p2) × with s1≤ s2and p1≤ p2, where Ξ Ψ ̄ is sublinear with Ξ(x) ≤ t and ρ, σ are nondecreasing functions on +such that ρ(t) < (1 -k)t and σ(t) < (1 -k)kt for all t > 0 and for some fixed k (0, 1).
  1. (3)
    The two functions Γ, ϒ: + [0, 1) given by
    Γ ( t ) = 0 if  t = 0 , ρ ( t ) ( 1 - k ) t if  t > 0 , ϒ ( t ) = 0 if  t = 0 , σ ( t ) ( 1 - k ) t if  t > 0 ,
     
are such that ( Γ , ϒ , ϒ ) S 3 , Γ + 2ϒ < 1.
  1. (4)

    F ( x , t , s , 0 ) s 0 t k ( x - ξ , t - τ ) d ξ d τ f o r a l l s 0 .

     
  2. (5)

    F is bounded for bounded s and p.

     

Then, the existence and uniqueness of the solution of the system (3.1) is affirmative.

It is essential to note that the problem (3.1) is equivalent (under the assumption of Theorem 3.1) to the integral equation:
u ( x , t ) = - k ( x - ξ , t ) φ ( ξ ) d ξ + 0 t - k ( x - ξ , t - τ ) F ( ξ , τ , u ( ξ , τ ) , u x ( ξ , τ ) ) d ξ d τ
(3.2)
for all x and 0 < tT, where
k ( x , t ) : = 1 4 π t e - x 2 4 t

for all x and t > 0. The system (3.1) possesses a unique solution if and only if the equation (3.2) possesses a unique solution u such that u and u x are both continuous and bounded for all x and 0 < t ≤ T.

Define a mapping Λ: Ω ω Ω ω by
( Λ u ) ( x , t ) : = - k ( x - ξ , t ) φ ( ξ ) d ξ + 0 t - k ( x - ξ , t - τ ) F ( ξ , τ , u ( ξ , τ ) , u x ( ξ , τ ) ) d ξ d τ

for all (x, t) × I. Then the problem of finding the solution to the equation (3.2) is equivalent to the problem of finding the fixed point of Λ.

Proof (Theorem 3.1). It is easy to see that the mapping Λ is nondecreasing by the definition. Let u, v Ω ω with u v. Suppose that uv. Besides, we have
1 1 + λ ( Λ v ) ( x , t ) - ( Λ u ) ( x , t ) 1 1 + λ 0 t - k ( x - ξ , t - τ ) | F ( ξ , τ , v ( ξ , τ ) , v x ( ξ , τ ) ) - F ( ξ , τ , u ( ξ , τ ) , u x ( ξ , τ ) ) | d ξ d τ 0 t - k ( x - ξ , t - τ ) c F 1 1 + λ + η ( λ ) ρ Ξ 1 1 + λ v ( ξ , τ ) - u ( ξ , τ ) + v x ( ξ , τ ) - u x ( ξ , τ ) + 1 1 + λ σ Ξ 1 1 + λ v ( ξ , τ ) - u ( ξ , τ ) + v x ( ξ , τ ) - u x ( ξ , τ ) d ξ d τ c F 1 1 + λ + η ( λ ) ρ ( Ξ ( ω λ ( u , v ) ) ) + 1 1 + λ σ ( Ξ ( ω λ ( u , v ) ) ) 0 t - k ( x - ξ , t - τ ) d ξ d τ c F 1 1 + λ + η ( λ ) ρ ( Ξ ( ω λ ( u , v ) ) ) + 1 1 + λ σ ( Ξ ( ω λ ( u , v ) ) ) T .
(3.3)
Similarly, we have
1 1 + λ ( Λ v ) x ( x , t ) - ( Λ u ) x ( x , t ) c F 1 1 + λ + η ( λ ) ρ ( Ξ ( ω λ ( u , v ) ) ) + 1 1 + λ σ ( Ξ ( ω λ ( u , v ) ) ) 0 t - | k x ( x - ξ , t - τ ) | d ξ d τ 2 π - 1 2 T - 1 2 c F 1 1 + λ + η ( λ ) ρ ( Ξ ( ω λ ( u , v ) ) ) + 1 1 + λ σ ( Ξ ( ω λ ( u , v ) ) ) .
(3.4)
Note that by (2), we have supt≥ 0ϒ(t) ≤ k < 1. Together with (3.3) and (3.4), we obtain
ω λ ( Λ u , Λ v ) ( T + 2 π - 1 2 T 1 2 ) c F 1 1 + λ + η ( λ ) ρ ( Ξ ( ω λ ( u , v ) ) ) + 1 1 + λ σ ( Ξ ( ω λ ( u , v ) ) ) 1 1 + λ + η ( λ ) ρ ( Ξ ( ω λ ( u , v ) ) ) + 1 1 + λ σ ( Ξ ( ω λ ( u , v ) ) ) = | | u - v | | 1 + λ + η ( λ ) ρ ( Ξ ( ω λ ( u , v ) ) ) | | u - v | | + | | u - v | | 1 + λ σ ( Ξ ( ω λ ( u , v ) ) ) | | u - v | | ω λ + η ( λ ) ( u , v ) ρ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( u , Λ u ) σ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( v , Λ v ) σ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( Λ u , Λ v ) σ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) ω λ + η ( λ ) ( u , v ) ρ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( u , Λ u ) σ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( v , Λ v ) σ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( Λ u , Λ v ) ϒ ( ω λ ( u , v ) ) ω λ + η ( λ ) ( u , v ) ρ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( u , Λ u ) σ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + ω λ ( v , Λ v ) σ ( Ξ ( ω λ ( u , v ) ) ) ω λ ( u , v ) + k ω λ ( Λ u , Λ v ) ω λ + η ( λ ) ( u , v ) ρ ( Ξ ( ω λ ( u , v ) ) ) Ξ ( ω λ ( u , v ) ) + ω λ ( u , Λ u ) σ ( Ξ ( ω λ ( u , v ) ) ) Ξ ( ω λ ( u , v ) ) + ω λ ( v , Λ v ) σ ( Ξ ( ω λ ( u , v ) ) ) Ξ ( ω λ ( u , v ) ) + k ω λ ( Λ u , Λ v ) .
Further, we obtain
ω λ ( Λ u , Λ v ) ω λ + η ( λ ) ( u , v ) Γ ( Ξ ( ω λ ( u , v ) ) ) + ω λ + ζ ( λ ) ( u , Λ u ) ϒ ( Ξ ( ω λ ( u , v ) ) ) + ω λ + μ ( λ ) ( v , Λ v ) ϒ ( Ξ ( ω λ ( u , v ) ) ) .
Moreover, since ξ is a sublinear (real) function in the class Ψ, it follows that
Ξ ( ω λ ( Λ u , Λ v ) ) Ξ ( ω λ + η ( λ ) ( u , v ) ) Γ ( Ξ ( ω λ ( u , v ) ) ) + Ξ ( ω λ + ζ ( λ ) ( u , Λ u ) ) ϒ ( Ξ ( ω λ ( u , v ) ) ) + Ξ ( ω λ + μ ( λ ) ( v , Λ v ) ) ϒ ( Ξ ( ω λ ( u , v ) ) ) .

For the case u = v, it is obvious that the above inequality is satisfied. Thus, we now have the inequality (2.1) holds for any comparable u, v Ω ω .

Note that any constant functions are contained in Ω. Now, for any u, v Ω ω , we may choose a constant function w Ω ω for which u, v w and θ w. Consequently, we have w(x, t) = ||w|| for all (x, t) × I. Also, observe that this w attains the following:
( Λ w ) ( x , t ) = - k ( x - ξ , t ) φ ( ξ ) d ξ + 0 t - k ( x - ξ , t - τ ) F ( ξ , τ , | | w | | , 0 ) d ξ d τ - k ( x - ξ , t ) φ ( ξ ) d ξ + | | w | | | | w | | = w ( x , t ) .

Hence, the condition (2.2) is satisfied. Therefore, by applying the Theorems 2.1 and 2.2, the result follows. This completes the proof. ■

Declarations

Acknowledgements

The authors were supported by the Higher Education Research Promotion and National Research University Project of Thailand, Office of the Higher Education Commission (NRU-CSEC No.55000613). This research was partially finished at Department of Mathematics Education and the RINS, Gyeongsang National University, Chinju, Korea, while the first and third authors visit here. Also, the second author was supported by the Basic Science Research Program through the National Research Foundation of Korea (NRF) funded by the Ministry of Education, Science, and Technology (Grant no. 2011-0021821). Furthermore, the authors are grateful for the reviewers for the careful reading of the article and for the suggestions which improved the quality of this work.

Authors’ Affiliations

(1)
Department of Mathematics, Faculty of Science, King Mongkut's University of Technology Thonburi, Bangkok, 10140, Thailand
(2)
Department of Mathematics Education and the RINS, Gyeongsang National University, Chinju, 660-701, Korea

References

  1. Golubović Z, Kadelburg Z, Radenović S: Coupled coincidence points of mappings in ordered partial metric spaces. Abstr Appl Anal 2012, 2012: 18. Article ID 192581Google Scholar
  2. Khamsi MA, Latif A, Al-Sulami H: KKM and Ky Fan theorems in modular function spaces. Fixed Point Theory Appl 2011, 2011: 57. 10.1186/1687-1812-2011-57MathSciNetView ArticleGoogle Scholar
  3. Khamsi MA: Quasicontraction mappings in modular spaces without Δ2-condition. Fixed Point Theory Appl 2008, 2008: 6. Article ID 916187MathSciNetView ArticleGoogle Scholar
  4. Kuaket K, Kumam P: Fixed points of asymptotic pointwise contractions in modular spaces. Appl Math Lett 2011, 24: 1795–1798. 10.1016/j.aml.2011.04.035MathSciNetView ArticleGoogle Scholar
  5. Amini-harandini A: Fixed point theory for generalized quasicontraction maps in vector modular spaces. Comput Math Appl 2011, 61: 1891–1897. 10.1016/j.camwa.2011.02.021MathSciNetView ArticleGoogle Scholar
  6. Aydi H, Nashine HK, Samet B, Yazidi H: Coincidence and common fixed point results in partially ordered cone metric spaces and applications to integral equations. Nonlinear Anal 2011, 74(17):6814–6825. 10.1016/j.na.2011.07.006MathSciNetView ArticleGoogle Scholar
  7. Aydi H: Common fixed point results for mappings satisfying ( ψ , ϕ )-weak contractions in ordered partial metric spaces. Int J Math Stat 2012, 12(2):53–64.MathSciNetGoogle Scholar
  8. Sintunavarat W, Kumam P: Weak condition for generalized multi-valued ( f , α , β )-weak contraction mappings. Appl Math Lett 2011, 24: 460–465. 10.1016/j.aml.2010.10.042MathSciNetView ArticleGoogle Scholar
  9. Sintunavarat W, Cho YJ, Kumam P: Common fixed point theorems for c -distance in ordered cone metric spaces. Comput Math Appl 2011, 62: 1969–1978. 10.1016/j.camwa.2011.06.040MathSciNetView ArticleGoogle Scholar
  10. Mongkolkeha C, Kumam P: Fixed point theorems for generalized asymptotic pointwise ρ -contraction mappings involving orbits in modular function spaces. Appl Math Lett 2012: [http://dx.doi.org/10.1016/j.aml.2011.11.027]
  11. Geraghty M: On contractive mappings. Proc Am Math Soc 1973, 40: 604–608. 10.1090/S0002-9939-1973-0334176-5MathSciNetView ArticleGoogle Scholar
  12. Amini-Harandi A, Emani H: A fixed point theorem for contraction type maps in partially ordered metric spaces and application to ordinary differential equations. Nonlinear Anal 2010, 72: 2238–2242. 10.1016/j.na.2009.10.023MathSciNetView ArticleGoogle Scholar
  13. Eshaghi Gordji M, Ramezani M, Cho YJ, Pirbavafa S: A generalization of Geraghty's theorem in partially ordered metric spaces and application to ordinary differential equations. Fixed Point Theory Appl 2012, 2012: 74.MathSciNetView ArticleGoogle Scholar
  14. Chistyakov VV: Modular metric spaces, I: basic concepts. Nonlinear Anal 2010, 72: 1–14. 10.1016/j.na.2009.04.057MathSciNetView ArticleGoogle Scholar
  15. Nakano H: Modulared Semi-Ordered Linear Spaces. In Tokyo Mathematics Book Series. Volume 1. Maruzen Co., Tokyo; 1950.Google Scholar
  16. Nakano H: Topology and Linear Topological Spaces. In Tokyo Mathematics Book Series. Volume 3. Maruzen Co., Tokyo; 1951.Google Scholar
  17. Kumam P: Some geometric properties and fixed point theorem in modular spaces. In Fixed Point Theorem and its Applications. Edited by: Garcia Falset J, Fuster L, Sims B. Yokohama Publishers, Yokohama; 2004:173–188.Google Scholar
  18. Kumam P: Fixed point theorems for nonexpansive mappings in, odular spaces. Arch Math (BRONO) 2004, 40(4):345–353.MathSciNetGoogle Scholar
  19. Kumam P: On uniform opial condition and uniform Kadec-Klee property in modular spaces. J Interdiscip Math 2005, 8(3):377–385.MathSciNetView ArticleGoogle Scholar
  20. Kumam P: On nonsquare and Jordan-Von Neumann constants of modular spaces. Southeast Asian Bull Math 2006, 30(1):67–77.MathSciNetGoogle Scholar
  21. Mongkolkeha C, Kumam P: Common fixed point for generallized weak contraction mapping in modular spaces. Sci Math Japon 117–127. e-2012 (online)Google Scholar
  22. Cho YJ, Saadati R, Sadeghi G: Quasi-contractive mappings in modular metric spaces. J Appl Math 2012, 2012: 5. Article ID 907951MathSciNetGoogle Scholar
  23. Chaipunya P, Mongkolkeha C, Sintunavarat W, Kumam P: Fixed-point theorems for multivalued mappings in modular metric spaces. Abstr Appl Anal 2012, 2012: 14. Article ID 503504Google Scholar
  24. Mongkolkeha C, Sintunavarat W, Kumam P: Fixed point theorems for contraction mappings in modular metric spaces. Fixed Point Theory Appl 2011, 2011: 93. 10.1186/1687-1812-2011-93MathSciNetView ArticleGoogle Scholar

Copyright

© Chaipunya et al; licensee Springer. 2012

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Advertisement